Relationship between Biological, Training, and Physical Fitness Variables in the Expression of Performance in Non-Professional Runners - Mabliny Thuany; Thayse Natacha Gomes; Marcos B. Almeida (MDPI AG, 2021)
Sports performance is a multifactorial trait that can be associated with individual and environmental characteristics. In this study, the sample comprised 35 male runners, enrolled in the "InTrack" project. Information regarding variables related to runners' training was obtained via an online questionnaire, while anthropometric and body composition variables, as well as physical fitness components (muscular power, isometric strength, local muscular endurance, agility, and aerobic capacity) were measured, and a global physical fitness score (based on physical fitness components measured) was computed. The Weltman test (3200 m) was used to estimate runners' pace and their stride frequency. Linear regression was used, taking the running pace as dependent variable. The final model, comprising biological, physical fitness, spatiotemporal, and training variables, explained 86% of the running performance variance. Muscular power (β = −1.02; 95% CI = (−1.69)-(−0.35)), abdominal muscle endurance (β = −4.81; 95% CI = (−7.52)-(−2.10)), isometric strength (β = −422.95; 95% CI = (−689.65)-(−156.25)), global physical fitness (β = 27.14; 95% CI = 9.52-45.03), and stride frequency (β = −2.99; 95% CI = (−4.29)-(−1.69)) were significantly associated with performance, meaning that better results in tests and increasing the stride frequency leads to better performance. Individual characteristics and physical fitness components were demonstrated to be significant predictors for running performance.